Περιβαλλοντικές επιπτώσεις από την κατασκευή και λειτουργία γηπέδων γκολφ στην Κύπρο - Μηνά, Φίλιππος (Τμήμα Επιστήμης και Τεχνολογίας Περιβάλλοντος, Σχολή Γεωτεχνικών Επιστημών και Διαχείρισης Περιβάλλοντος, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2015)
Firstly, it must be noted that in order to be built a golf, as in any project, based on the legislation an Assessment Study of Environmental Impact must be done. This study aims to determine whether the project creates environmental impacts and accordingly be approved or not by the Department of Environment. In the current Dissertation analyses of the impact by golf courses in Cyprus are being done during construction and operation. Emphasis is given to the consequences for the environment and recommendations are provided to address those impacts. This study was written having in mind the requirements of law 140(I)/2005. Information were sourced from the bibliography, existing golfs operating in Cyprus were visited in which views were taken from the owners. The main parameters taken into consideration are water, land use and ecology of Cyprus. The construction of golf courses drives to dust creation, partial deterioration of the local topography and the biological environment, and noise of the various equipment used. Concerning the operation of a golf course, the main impacts related to the excessive use of fertilizers and pesticides which may cause contamination of surface and groundwater. In addition, another problem are the huge amounts of water needed to irrigate the lawn and the water source to meet those needs. In this study it was showed that apart from the negative impact caused by golf courses are respectively positive and which come into conflict with environmental damage. The development of the economy by the quality tourism increase and the improvement of the landscape’s aesthetics, are the most important benefits caused to Cyprus from the golf operations. In conclusion, we come to that in Cyprus, as in other countries the main problem for golf courses that deserves special treatment is the change in land use and large amounts of water needed to irrigate the land.
Keywords: Golf courses; Environmental impacts; Cyprus; Γήπεδα γκολφ; Περιβαλλοντικές επιπτώσεις; Κύπρος